2015
DOI: 10.1016/j.bpj.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxy Fatty Acid Enantiomers of Gb 3 Impact Shiga Toxin Binding and Membrane Organization

Abstract: Shiga toxin subunit B (STxB) binding to its cellular receptor Gb3 leads to the formation of protein-lipid clusters and bending of the membrane. A newly developed synthetic route allowed synthesizing the biologically most relevant Gb3-C24:1 2OH species with both, the natural (Gb3-R) as well as the unnatural (Gb3-S) configuration of the 2OH group. The derivatives bind STxB with identical nanomolar affinity, while the propensity to induce membrane tubules in giant unilamellar vesicles is more pronounced for Gb3-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 31 publications
2
56
1
Order By: Relevance
“…To see this figure in color, go online. of a protein layer that is determined by the height of the layer as well as the surface coverage (27,31,32,42). For ezrin bound to DOGS-Ni-NTA or PIP 2 , the change in OT as a result of protein surface coverage is reflected by the increase in DOT as a function of increasing receptor lipid content in the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To see this figure in color, go online. of a protein layer that is determined by the height of the layer as well as the surface coverage (27,31,32,42). For ezrin bound to DOGS-Ni-NTA or PIP 2 , the change in OT as a result of protein surface coverage is reflected by the increase in DOT as a function of increasing receptor lipid content in the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…RIfS is an optical technique that allows label-free investigations of protein binding to a specific receptor lipid embedded in SLBs (27,(31)(32)(33)(34)(35). The adsorption process is detected as an increase in optical thickness, OT ¼ n d, i.e., the product of the refractive index n and the physical layer thickness d. RIfS experiments were employed to analyze whether ezrin wt or ezrin T567D adsorbed to either the receptor lipid DOGS-Ni-NTA or PIP 2 results in a difference in OT.…”
Section: Analysis Of Ezrin-lipid Interactions By Rifsmentioning
confidence: 99%
“…The largest protein layer thickness was found for PI(3,4,5)P 3 -doped membranes with d protein-max ϭ 2.8 Ϯ 0.3 nm. Assuming a maximum protein surface coverage of 56% according to the scaled particle theory (25) and a diameter of the PH domain of 4.2 nm as obtained from the crystal structure (12), one would expect a protein layer thickness of 2.4 nm. Comparing the theoretical and experimental values, we conclude that full protein coverage is reached in the case of PI(3,4,5)P 3 , whereas for the other PIPs, a lower surface coverage is found.…”
Section: Resultsmentioning
confidence: 99%
“…3A) (19 -21). RIfS is a well established technique to quantitatively monitor proteinreceptor interactions at solid-supported membranes (22)(23)(24)(25).…”
mentioning
confidence: 99%
“…For example, a recent study was able to demonstrate that the chirality of Gb3 influences protein-membrane organization and moreover affects the propensity of tubule formation in GUVs. The authors concluded, that the protein cluster formation depends on the structure of the Gb3 fatty acid chains and area demand of unsaturated fatty acids, which, in combination, impact membrane bending[105].An additional study simulating the effects of varying Gb3 concentrations (0, 12, 25, 50 and 100 mol-%) and degree of saturation confirmed that no tubule formation occurred for saturated Gb3 species. This was owing to the formation of a rigid immobile phase, resistant to bending in view of a high energetic cost.…”
mentioning
confidence: 60%